2014
DOI: 10.1101/cshperspect.a019661
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Pathogens: Survival and Replication within Macrophages

Abstract: The innate immune system is a critical line of defense against pathogenic fungi. Macrophages act at an early stage of infection, detecting and phagocytizing infectious propagules. To avoid killing at this stage, fungal pathogens use diverse strategies ranging from evasion of uptake to intracellular parasitism. This article will discuss five of the most important human fungal pathogens (Candida albicans, Aspergillus fumigatus, Cryptococcus neoformans, Coccidiodes immitis, and Histoplasma capsulatum) and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 94 publications
3
79
0
Order By: Relevance
“…Even though C. albicans filaments within macrophages in vitro 31, recent findings in a zebrafish model50 suggest that some macrophages can inhibit filamentation in vivo 51 and C. albicans DEGs in the zebrafish model showed a significant overlap with the transcriptome in the liver. Furthermore, phagocytosis by PMNs prevents C. albicans filamentation1352.…”
Section: Resultsmentioning
confidence: 99%
“…Even though C. albicans filaments within macrophages in vitro 31, recent findings in a zebrafish model50 suggest that some macrophages can inhibit filamentation in vivo 51 and C. albicans DEGs in the zebrafish model showed a significant overlap with the transcriptome in the liver. Furthermore, phagocytosis by PMNs prevents C. albicans filamentation1352.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of C. albicans to cause invasive infections depends on its dynamic and complex interactions with cells of the innate immune system, such as macrophages (12,38,39). Strikingly, phagocytosed C. albicans cells form hyphae that facilitate their escape, and we have shown that this is induced by a fungus-driven neutralization of the phagolysosome (24,25).…”
Section: Resultsmentioning
confidence: 88%
“…In vitro models include the use of cell lines; primarily, monocytes, 3 and macrophages, 4 and also dendritic cells, neutrophils, eosinophils, and lymphocytes. 5 In addition, in vivo models have been established and include vertebrate models of mouse, rat, and rabbit.…”
mentioning
confidence: 99%